2002
DOI: 10.1007/s00445-002-0241-2
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of magnetic susceptibility studies of depositional processes in the Campanian Ignimbrite, Italy

Abstract: The late Pleistocene trachytic Campanian Ignimbrite underlies much of the Campanian Plain near Naples, Italy, and occurs in valleys in the mountainous area surrounding the plain out to about 80 km from its source, the Campi Flegrei caldera. At sites within 15 km of the Campi Flegrei, anisotropy of magnetic susceptibility (AMS) principal directions indicate that, in the absence of significant topography, deposition came from a flow moving in a roughly radial direction. AMS studies of the more distal ignimbrite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 31 publications
3
67
0
Order By: Relevance
“…By the early 1990s, the technique began to be used to study flow and depositional processes in ignimbrites (Fisher et al 1993;Ort 1993;Baer et al 1997;Le Pennec et al 1998;Ort et al 2003;Porreca et al 2003;Pioli et al 2008). These authors found that the shape of the ellipsoid and the grouping of axes could be used to interpret depositional processes, which could then reveal details of flow processes.…”
Section: Anisotropy Of Magnetic Susceptibility (Ams) As Magmatic Flowmentioning
confidence: 99%
“…By the early 1990s, the technique began to be used to study flow and depositional processes in ignimbrites (Fisher et al 1993;Ort 1993;Baer et al 1997;Le Pennec et al 1998;Ort et al 2003;Porreca et al 2003;Pioli et al 2008). These authors found that the shape of the ellipsoid and the grouping of axes could be used to interpret depositional processes, which could then reveal details of flow processes.…”
Section: Anisotropy Of Magnetic Susceptibility (Ams) As Magmatic Flowmentioning
confidence: 99%
“…We infer that change in the flow imbrications angle and K 1 directions across the area reflect variations in local slope which increases the overall dispersion of the transport data. Indeed, the effect of subtle topography on AMS directional data has been recognized in other ignimbrites (e.g., [29][30][31]). …”
Section: Directional Data: Flow Directions and Identification Of Emismentioning
confidence: 99%
“…In ignimbrite studies, foliation, lineation and imbrication of foliation have been found closely related with flow directions and local flow dynamics-e.g. laminar or turbulent flow- (Inconorato et al, 1983;Knight et al, 1986;MacDonald and Palmer, 1990;Hillhouse and Wells, 1991;Cagnoli and Tarling, 1996;Palmer and MacDonald, 1999;Ort et al, 1999Ort et al, , 2003Alva-Valdivia et al, 2005).…”
Section: Introductionmentioning
confidence: 99%